Public or private management of universities: Which is the most efficient option for a public policy in higher education in Colombia? - Morales-Piñero, Juan; Niño-Muñoz, Diana; Lesmes-Cardenas, Diana (Education Policy Analysis Archives, 2022)
The State is known as the guarantor of the higher education service. However, it does not always have the operational capacity to guarantee adequate coverage in the provision of the service. For this reason, it delegates this responsibility to public and private actors, although it could compromise the quality of the service. In this sense, the objective of this article is to compare, from a holistic measurement, the efficiency between public and private management of Colombian universities to guide the formulation of public policies in higher education. To this end, an efficiency metafrontier was estimated using data envelopment analysis (DEA), including formal unemployment as a bad output variable, to collect information on the undesired effect on the service provision of the 122 universities analyzed. Although it was not possible to prove significant differences between public and private management of the university, it was possible to evidence scenarios where public policy can help improve the system, considering differences by type of property and geographic location. The main conclusions highlight the importance of regional particularities to selectively consolidate public-private partnerships and improve the performance of the system.